Transforming the Chemical Structure and Bio‐Nano Activity of Doxorubicin by Ultrasound for Selective Killing of Cancer Cells. Issue 13 (18th February 2022) - Bhangu, Sukhvir Kaur; Fernandes, Soraia; Beretta, Giovanni Luca; Tinelli, Stella; Cassani, Marco; Radziwon, Agata; Wojnilowicz, Marcin; Sarpaki, Sophia; Pilatis, Irinaios; Zaffaroni, Nadia; Forte, Giancarlo; Caruso, Frank; et al.
Abstract: Reconfiguring the structure and selectivity of existing chemotherapeutics represents an opportunity for developing novel tumor‐selective drugs. Here, as a proof‐of‐concept, the use of high‐frequency sound waves is demonstrated to transform the nonselective anthracycline doxorubicin into a tumor selective drug molecule. The transformed drug self‐aggregates in water to form ≈200 nm nanodrugs without requiring organic solvents, chemical agents, or surfactants. The nanodrugs preferentially interact with lipid rafts in the mitochondria of cancer cells. The mitochondrial localization of the nanodrugs plays a key role in inducing reactive oxygen species mediated selective death of breast cancer, colorectal carcinoma, ovarian carcinoma, and drug‐resistant cell lines. Only marginal cytotoxicity (80–100% cell viability) toward fibroblasts and cardiomyocytes is observed, even after administration of high doses of the nanodrug (25–40 µg mL −1 ). Penetration, cytotoxicity, and selectivity of the nanodrugs in tumor‐mimicking tissues are validated by using a 3D coculture of cancer and healthy cells and 3D cell‐collagen constructs in a perfusion bioreactor. The nanodrugs exhibit tropism for lung and limited accumulation in the liver and spleen, as suggested by in vivo biodistribution studies. The results highlight the potential of this approach to transform the structure and bioactivity of anticancer drugs and antibiotics bearing sono‐active moieties. Abstract : The ultrasonic transformation of doxorubicin into a tumor selective nanodrug is presented. The nanodrug maintains the antiproliferative activity against several cancer cell lines without being toxic to healthy cells as verified in 2D/3D coculture. The nanodrug associates with lipid rafts on mitochondria membranes to produce cytotoxic reactive oxygen species. In vivo study reveals accumulation of the nanodrug in the lung.